Development of E-Module Based on Problem Based Learning Assisted with Scratch Applications to Improve Students Computational Thinking Skills - Handayani, Fitri; Fitria, Yanti; Ahmad, Syafri; Zen, Zelhendri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop a valid, practical, and effective problem-based learning e-module to improve the computational thinking skills of fifth-grade elementary school students. The research method used was Research and Development, using the ADDIE development model. The research instruments used were validation questionnaires, practicality questionnaires for students and teachers, and pretest and posttest question sheets to measure students’ abilities. While the data analysis technique to test the validity and practicality using a Likert scale, while the product effectiveness test was carried out using the Pretest-Posttest Control Group Design and analyzed using SPSS. The results of the research showed that the validity results based on lesson plans obtained a value of 94.44% (very valid), material expert validators 90.48% (very valid), linguists 92.86% (very valid), and media experts 89.6% (very valid). The practical results can be seen from the student response of 90.42% or very practical, and the teacher’s response of 93,52 % or very practical. At the same time, the effectiveness test from the results of the pretest and posttest obtained that count> table, namely 15,499 > 1,711 and Sig (2-tailed) 0,000 <0.05, so it can be concluded that there is an average difference in students’ computational thinking abilities from the results of the pretest to the results of the posttest in the experimental class. Furthermore, the effectiveness test based on N-gain was obtained at 60.6203 or 60.6%, including the quite effective category. So, the development of PBL-based e-modules assisted by scratch applications to improve the computational thinking skills of Grade V elementary school students is declared valid, practical, and effective.